Personal risk factors and types of sport associated with drive for thinness and drive for muscularity in NextGen athletes - Maurin, Juliette; Labossière, Sophie; Pomerleau-Fontaine, Lara; Boudreault, Véronique; Brassard, Sophie; Dion, Jacinthe; Durand-Bush, Natalie; Parent, Sylvie; Soulard, Amélie (Frontiers in Nutrition, 2024)
Professional and student-athletes are at risk of developing symptoms of eating disorders (ED), including drive for thinness and muscularity due to personal risk factors (e.g. low self-esteem) and sport-specific characteristics (e.g. sport requirements). However, limited studies have focused on ED symptoms among NextGen athletes (identified in Canada as élite or relève) who compete at the provincial, national, and international levels but are not yet part of national teams. As such, they have access to fewer financial resources and support from their sport federations, which can create additional stress for these athletes. The present study aimed to identify personal risk factors and types of sports associated with (a) drive for thinness and (b) drive for muscularity in NextGen athletes. These athletes (n=254) aged between 14 and 25 years old completed an online questionnaire. Perfectionism, self-esteem in sport, drive for thinness, and drive for muscularity were respectively assessed by the Multidimensional Inventory of Perfectionism in Sport, the Sport State Self-Esteem Scale, the Eating Attitude Test-24, and the Drive for Muscularity Scale. Other personal risk factor (e.g., athletic status) were measured using in-house questions. Each personal risk factor was included in two multiple linear regressions, respectively, to determine which factors were most associated with drive for thinness and drive for muscularity. Analyses revealed that perfectionist aspirations during training were linked to a stronger desire for thinness. In addition, not being in school or not having a job were also linked to a stronger desire for thinness. Several variables were found to be associated with a greater desire for muscularity: being a male athlete, playing team sport, weight category sport or endurance sport (as opposed to aesthetic sport), having elite status, being less satisfied with one's current sporting performance and having higher perfectionist aspirations during training. This study offers initial insights into the factors influencing EDs among NextGen athletes, which provides a foundation for deeper exploration and the creation or modification of targeted interventions. These findings can guide sport organizations in creating guidelines and programs to better support the next generation of national athletes (e.g., create programs to help athletes maintain investments outside sport).